Deciphering neurodegeneration: models and methods - Lewis, Patrick A. (Henry Stewart Talks, 2014)
Deciphering Neurodegeneration: Models and Methods, The challenge of neurodegeneration, Huge diversity in cell types, Nature versus nurture, Reductionism versus systems biology, Cellular models, Yeast, Primary cells, Cell lines, Stem cells, Model organisms, Caenorhabditis elegans, Drosophila melanogaster, Zebrafish, Danio rerio, Rodents, Molecular biology approaches, Knock out and knock in, Genomic editing, RNAi, Overexpression, Gene expression, rtPCR, Microarrays, RNAseq, Protein analysis, Immunoblot, ELISA, Mass spec and proteomics, Microscopy – Immunocytochemistry, Live cell imaging, Electrophysiology